1994
DOI: 10.5694/j.1326-5377.1994.tb125943.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for retinopathy in adolescents with type 1 diabetes

Abstract: Objectives To establish the prevalence of, and risk factors associated with, diabetic retinopathy in an Australian adolescent diabetes clinic population. Design A prospective longitudinal study; baseline findings. Patients Two hundred and fifty‐five patients with Type 1 (insulin‐dependent) diabetes mellitus assessed by our service were studied. Entry criteria were: age 11.0‐19.9 years; diabetes duration of at least two years; and gradable fundus photographs of at least one eye. Main outcome measures The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…The DR prevalence among the T1DM was reported to be lower in Asia with the lowest prevalence in India (13.4%), followed by China (14%) . In Australia and New Zealand, the DR prevalence rate ranged from 25% to 42% . The prevalence of DME is related to the disease duration, with low rates of DME within 5 years of T1DM diagnosis, increasing to 29% at 20 years .…”
Section: Global Epidemiology Of Drmentioning
confidence: 96%
“…The DR prevalence among the T1DM was reported to be lower in Asia with the lowest prevalence in India (13.4%), followed by China (14%) . In Australia and New Zealand, the DR prevalence rate ranged from 25% to 42% . The prevalence of DME is related to the disease duration, with low rates of DME within 5 years of T1DM diagnosis, increasing to 29% at 20 years .…”
Section: Global Epidemiology Of Drmentioning
confidence: 96%
“…19 Early screening and appropriate intervention have been demonstrated to be very effective in reducing visual impairment and blindness attributed to retinopathy. 20 Because of a high prevalence of chronic diseases (such as diabetes mellitus) in the elderly population, we should pay more attention to renewed efforts for effective public health initiatives. Compared with other related eye diseases, age-related macular degeneration and corneal diseases had relatively lower prevalence among the elderly population in the present study.…”
Section: Associated Factors Related To Visual Disabilitymentioning
confidence: 99%
“…4 Early screening and appropriate intervention have been shown to be very effective in reducing visual loss and blindness attributed to DR. 5 The United Kingdom Prospective Diabetes Study (UKPDS) also showed that careful ophthalmic assessment is important, since DR is common in newly diagnosed type 2 diabetic patients. 6 In addition, the duration of diabetes, [7][8][9][10][11][12][13] age at examination, 10,13 type of diabetes treatment, 14,15 blood pressure, 6,16 serum cholesterol, 7 and body mass index (BMI) 10 have been reported to be associated with DR among type 2 diabetic patients.…”
mentioning
confidence: 99%